Media neglect of Indigenous student performance in the Programme for International Student Assessment (PISA) 2001–2015. Issue 1 (17th August 2021) - Davis, Edward Rock; Wilson, Rachel; Evans, John Robert
Abstract: This research explores media reporting of Indigenous students' Programme for International Student Assessment (PISA) results in two national and 11 metropolitan Australian newspapers from 2001 to 2015. Of almost 300 articles on PISA, only 10 focused on reporting of Indigenous PISA results. While general or non-Indigenous PISA results featured in media reports, especially at the time of the publication of PISA results, there was overwhelming neglect of Indigenous results and the performance gap. A thematic analysis of articles showed mainstream PISA reporting had critical commentary which is not found in the Indigenous PISA articles. The three themes identified include: a lack of teacher quality in remote and rural schools; the debate on Gonski funding recommendations and the PISA achievement gap between Indigenous and non-Indigenous students. This study concluded the overwhelming neglect is linked to media bias, which continues to drive mainstream media coverage of Indigenous Australians.